Відбитки камей із зібрання Катерини Скаржинської: атрибуція та реставрація - Кондратенко, Н.Г. (Сіверщина в історії України, 2024)
Стаття присвячена характеристиці зібрання відбитків камей Полтавського краєзнавчого музею імені Василя Кричевського, що походить із колекції Катерини Скаржинської – знаної меценатки, яка стоїть біля витоків закладу. Виготовлення відбитків камей розглянуто як окремий вид мистецтва, що зародився ще в античні часи та набув особливого поширення у добу Просвітництва. Розглянуто проблему традиційного нівелювання значення цих предметів у зібраннях музеїв України та світу. Проведено детальну атрибуцію музейної колекції відбитків камей, описано їх систематизацію в межах «дактиліотеки». Проаналізовано шлях їх надходження до закладу, долю в якості музейних предметів у вирі буремних подій ХХ ст. Окремо описано процес реставрації артефактів збірки, акцентовано увагу на особливостях їх збереження. Підкреслено їх відновлений експозиційний потенціал та загальну атрактивність. The article is dedicated to characteristics of the Vasyl Krychevsky Poltava Local Lore Museum gathering of cameo imprints, that came to museum from collection of Kateryna Skarzhynska, who was famous philanthropist as she gave her private ethnographical collection to the museum. Making cameo imprints of carved stones and their imitations developed side by side with glyptic art since Ancient Roman time. In the Renaissance period collectors started to unite cameo imprints into «dactyliothecas»; in the Enlightenment this kind of collecting reached its peak of popularity. New kind of entertainment for rich gatherers started to spread – making cameo imprints and replicas with own hands in specially equipped laboratories. Among the most famous lovers of this entertainment were even members of European royal families and their surroundings. Problem of traditional underestimating of these artifacts in Ukrainian and world museums is observed. Detailed attribution of museum cameo imprints collection is made, its systemization in «dactyliotheca» is described. Most images are connected with Roman Empire. Such plots of cameo imprints can be explained by interest to antique art and reflect collectors’ tastes and art tendencies in Europe during the Enlightenment period. Small number of cameo imprints with philosophers, writers and artists of the Renaissance period in museum collection proves thesis about plot preference to antique period, as these images served more as appendixes to classic dactyliothecas than their basis. Way of cameos camming to the museum and their faith during ruff events of the 20th c. is analyzed. Process of restoration of museum items is observed in details. Special attention is paid to peculiarities of their preserving. Their renovated expositional potential and attractiveness are outlined.